Implementation of Internet of Things-Based Bird & Mouse Pest Repellent Tools for Rice Plants - Suja’i, Ahmad; Samsumar, Lalu Delsi; Zaenudin, Zaenudin (Journal of Computer Science and Informatics Engineering, 2024)
The development of smart farming technology has developed rapidly, but in Montong Are Village, the majority of farmers still use conventional tools which are less effective in repelling pest birds and mice. This research aims to develop an Internet of Things (IoT) based bird and mouse pest repellent tool for rice plants to help farmers effectively repel pests on rice plants. Research methods include identifying needs through interviews, environmental observation, development, evaluation and improvement of prototypes. The results of this research show that this prototype can repel pest birds and mice automatically using PIR sensors and Ultrasonic sensors. Additionally, farmers can receive notifications via the Telegram app, allowing them to take immediate action if necessary. This system is very effective, makes things easier for farmers, and can repel pest birds and mice more efficiently than conventional tools which are less effective. The implementation of IoT technology provides innovative solutions to pest problems, increases agricultural productivity and reduces losses due to pests.